2021
DOI: 10.47278/journal.abr/2020.012
|View full text |Cite
|
Sign up to set email alerts
|

Blend of Flour With Vigna Radiata and Vigna Mungo Used in Muffins in Order to Increase Nutritional Properties

Abstract: Supplementation of foods is current intrigue due to increasing healthful mindfulness among consumers. Muffins can be effectively strengthened with protein-rich lentils to give advantageous nourishments, so as to enhance protein in the eating routine and sustenance. Fortification of lentil was attempted at 30, 40, and 50% to think about the nourishing, textural, practical, and physicochemical properties in muffins. Legumes in perception on their supplement profile appear to be perfect for incorporation in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Meat is a prominent source of protein in the average person's diet. Additionally, it has been shown that fortifying different lentils can ease the pressure on meat consumption ( 1 ). Since 1961, the amount of meat produced worldwide has more than quadrupled.…”
Section: Introductionmentioning
confidence: 99%
“…Meat is a prominent source of protein in the average person's diet. Additionally, it has been shown that fortifying different lentils can ease the pressure on meat consumption ( 1 ). Since 1961, the amount of meat produced worldwide has more than quadrupled.…”
Section: Introductionmentioning
confidence: 99%